2011
DOI: 10.1002/hrm.20434
|View full text |Cite
|
Sign up to set email alerts
|

Employees' attitudes toward organizational change: A literature review

Abstract: Organizations are increasingly required to improve their ability to enhance employees' support or acceptance for change initiatives. In studies that have examined the conditions in which employees support organizational change, researchers have focused on various attitudinal constructs that represent employees' attitudes toward organizational change. The constructs, which frequently serve as key variables in these studies, include readiness for change, commitment to change, openness to change, and cynicism abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
427
1
43

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 405 publications
(484 citation statements)
references
References 95 publications
13
427
1
43
Order By: Relevance
“…This finding is also in line with the readiness for change literature which suggests that the employees' readiness for change constitutes a crucial factor for positive attitudinal responses to change (e.g. Choi, 2011).…”
Section: Discussionsupporting
confidence: 90%
“…This finding is also in line with the readiness for change literature which suggests that the employees' readiness for change constitutes a crucial factor for positive attitudinal responses to change (e.g. Choi, 2011).…”
Section: Discussionsupporting
confidence: 90%
“…The impact of HR practices on organizational performance has been an important area of HRM research. The researchers has widely focused on the effect of Human Resource Management practices on organizational productivity and financial performance (Choi, 2011). Success in today's world business is lying behind the benefits and scales of operations and scale of economies.…”
Section: Introduce Hrm Practices and Labor Productivitymentioning
confidence: 99%
“…Organisational change can be a major stressor and is often associated with reduced wellbeing, job loss, and interpersonal conflict (Ashford, 1988;Schweiger & Denisi, 1991). Furthermore, employees' openness to change is associated with a range of positive work outcomes, including more job satisfaction, less work irritation, and lower intentions to quit (Wanberg & Banas, 2000), as well as whether change initiatives achieve the intended aims (Choi, 2011). On the other hand, employees who are resistant to change experience more distress and work less effectively when organisational change occurs (Oreg, 2003).…”
Section: Resistance To Changementioning
confidence: 99%
“…While attitudes towards particular changes are largely influenced by contextual factors and employees' specific attitudes toward those changes (for review, see Choi, 2011), research has found that attitudes towards change can also be influenced by dispositional factors. For example, Judge, Thoresen, Pucik, and Welbourne (1999) reported that openness to change is associated with factors relating to Positive Self-Concept (i.e.…”
Section: Resistance To Changementioning
confidence: 99%
See 1 more Smart Citation